TRANSFORMATION OF LABOUR MARKET INSTITUTIONS TO IMPROVE VOCATIONAL EDUCATION IN UKRAINE (Innovative professional education, 2024)
An analysis of the reasons for insufficient efficiency and quality of the vocational education system in Ukraine was carried out. Reasonably, in order to increase the efficiency of the labor market and the system of professional education, the need for: state intervention in the transformation of labor market institutions; implementation of a system of organizational and economic and legal measures regarding the transformation of the labor market for its efficiency, harmonization of the actions of its participants through the development of its information infrastructure to reduce its transaction costs.
Keywords: effectiveness of professional education, transformation of labor market institutions